Phosphorus recovery potential from sewage sludge by struvite precipitation: remodelling policy framework in Rajasthan, India - Ankit Srivastava; Kanika Saxena; Urmila Brighu (Water Science and Technology, 2024)
The manufacturing of fossil-based fertilizers by extraction of rock phosphate has contributed to carbon emissions and depleted the non-renewable phosphorus reserves. Sewage sludge, which is a waste product from Sewage Treatment Plants (STPs), is rich in phosphorus. The existing techniques for sludge management contribute to carbon emissions and ecological footprint. Struvite (raw fertilizer) and biochar recovery from sludge has emerged as viable methods to reduce carbon emission and ensure economic sustainability of STPs. In this work, the potential for phosphorus recovery and revenue generation is discussed for Rajasthan state in India. The fate of phosphorus and heavy metals in STPs is evaluated which indicates that about 70% of the phosphorus and trace amounts of metals end up in sewage sludge. Further, the power consumption is high in STPs due to industrial wastewater ingress. There is a need to bridge the gap between sewage treatment and generation in Rajasthan, improve STP performance before resource recovery inclusion at policy-level and scale-up. Mixing struvite with biochar can lead to safe application of struvite as raw fertilizer as heavy metals are sequestered by biochar. A business framework is developed to serve as a blueprint and potential model for linking technical and market viability. HIGHLIGHTS This article highlights the concept of integrated sewage management for conforming to discharge guidelines and resource recovery from sewage sludge.; The present policies for wastewater management in India are discussed.; The carbon footprint and revenue generation from struvite and biochar are discussed.; A business framework has been developed.; The fate of phosphorus and heavy metals in STPs is evaluated.;